A Nurse-Driven Protocol to Reduce Hospital-Acquired Clostridium difficile Infections. (4th October 2017) - Nanayakkara, Deepa; Mejia, Eveline; Nanda, Neha
Abstract: Background: Clostridium difficile infection (CDI) is one of the most common healthcare-associated infections. Timely diagnosis is key to reducing associated morbidity and costs. Healthcare-onset (HO) CDI is defined as infection diagnosed 72 hours after hospitalization. Centers for Medicare and Medicaid Services has established benchmarks for HO-CDI for hospitals, which are based on several factors including type of hospital and case mix index. There is a financial penalty if we are above the benchmark. In 2016, 20% of our community-onset C. difficile (CO-CDI) cases were misclassified as HO-CDI. In order to reduce this misclassification, we established a process to assist in early diagnosis. Methods: We designed and implemented a nurse-driven C. difficile screening protocol to assist in early identification of CO-CDI. Every patient admitted to Keck Hospital (KH) (401 beds) and Norris Comprehensive Cancer Center (35 beds) was screened for diarrhea within the past 24 hours. If diarrhea was present, additional questions were used to capture CO-CDI cases. A nursing order for C. difficile testing was activated for patients who met any of these criteria. Additionally, we used Bristol stool scale (BSS) to standardize stool collection. Only Bristol stool type 7 was accepted by laboratory for processing. Our study period was January 1 st through April 30 th, 2017 and our baseline period was January 1 st through April 30 th, 2016. Results: Screening protocol and BSS were introduced on January 1 st, 2017. During the baseline period, a total of 351 orders were placed with 31% within first 3 days of admission. During the study period, a total of 200 orders were placed with 43% within 3 days of admission. Compliance with using the screening tool was nearly 100%. Inter-rater reliability between nurses and lab for identifying the correct BSS was 100%. Baseline misclassification rate was 16%. With the introduction of this screening tool, misclassification decreased to 9%. The HO-CDI rate for the baseline period was 11.5 per 10, 000 patient-days and it decreased to 6.27 per 10, 000 patient-days in the study period. Conclusion: We have demonstrated a reduction in HO-CDI rates by establishing a process to assist in early identification of CO-CDI. Disclosures: All authors: No reported disclosures.